Blended-problem based learning: critical thinking skills and information literacy in cell learning - Vitta Yaumul Hikmawati; Yeni Surya Ningsih (JURNAL BIOEDUKATIKA, 2020)
Critical thinking skills and information literacy are two competencies that students need to have in the millennial era that is loaded with a wide range of types and sources of information. This research was conducted to investigate the effectiveness of blended-problem based learning through Google Classroom application to increase students critical thinking and information literacy in material about cell. This research was a quasi-experimental with pretest-posttest control group design. Two classes were selected randomly from eight Mathematics and Natural Science (MIPA) grade XI classes in state high school of SMA Negeri 1 Majalengka. The experiment group experienced blended-problem based learning and the control group received a conventional-problem based learning (PBL). Critical thinking skills were measured through a test consisting of essay questions with a reliability of 0.73. Information literacy competency was measured through a questionnaire using 26 items that had been tested for validity and reliability, resulting in an alpha coefficient of 0.896. Data were analyzed quantitatively using independent t-test and produced p-value of 0.021 and 0.018 for critical thinking skills and information literacy respectively. This shows that statistically there are significant differences in students critical thinking skills and information literacy between blended-PBL and conventional-PBL. This research indicates that the blended-PBL strategy can be implemented as a learning strategy, especially in Biology to prepare students for the 21st century challenges.